THE INFECTION WITH HELICOBACTER PYLORI FAVORS THE PRESENCE OF GIARDIA LAMBLIA IN THE GASTRIC MUCOSA – CASE PRESENTATION - Meliț Lorena Elena (Romanian Journal of Infectious Diseases, 2016)
Helicobacter pylori and Giardia lamblia are common worldwide. Helicobacter pylori is a favoring factor for the presence of Giardia lamblia in the stomach due to the neutralization of the gastric pH through the secretion of urease. We present the case of a 5-year-old child, with intermittent gastro-intestinal symptoms in the recent personal pathological history, admitted in the Pediatrics Clinic 1 Târgu Mureș for abdominal pain, nausea, loss of appetite and hematemesis. The superior digestive endoscopy revealed multiple hemorrhagic lesions of the gastric mucosa, and the pathological exam of the antral gastric mucosa identified the coexistence of Helicobacter pylori and Giardia lamblia. The evolution of the patient was favorable under the eradication therapy of the infection with Helicobacter pylori and the antiparasitic drugs, the control endoscopy revealing a gastric mucosa without macroscopically obvious modifications, and the pathological re-evaluation pointed out regenerative modifications of the gastric mucosa. The particularity of the case is represented by the identification of the parasite Giardia lamblia in the gastric mucosa, a physiologically acid environment, alkalinized by the urease secreted by Helicobacter pylori, therefore providing favorable conditions for the development of this parasite in a 5-year-old child, from a favorable socio-economic environment, with intermittent gastrointestinal symptoms in his recent personal pathological history.